Development of a linear motor based gantry - Brocoy, Jonel A.
Gantry systems used in industrial applications range from CAD plotters, pick-and-place operations used in manufacturing of small devices, such as ICs, to gantry cranes used in shipbuilding docks. Linear motors are now used in gantries due to their promising advantages. They provide higher accuracy and speed in terms of positioning and linear motion compared to the traditional belt-and-pulley, rack-and-pinion, screw, and rotary motor systems. We designed and implemented a control system and a power supply for the first dual axis linear motor gantry of YICAL. The structure, which will be used mainly for instructional and research purposes, was designed to have a target acceleration of 5 m/s² and maximum velocity of 0.3 m/s. A microcontroller was used as the main controller. A GUI was also developed to accept commands from the user to move the motors of the gantry.